The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/1365-2656.12168
|View full text |Cite
|
Sign up to set email alerts
|

Pollen mixing in pollen generalist solitary bees: a possible strategy to complement or mitigate unfavourable pollen properties?

Abstract: Summary1. Generalist herbivorous insects, which feed on plant tissue that is nutritionally heterogeneous or varies in its content of secondary metabolites, often benefit from dietary mixing through more balanced nutrient intake or reduced exposure to harmful secondary metabolites. Pollen is similarly heterogeneous as other plant tissue in its content of primary and secondary metabolites, suggesting that providing their offspring with mixed pollen diets might be a promising strategy for pollen generalist bees t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
127
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(133 citation statements)
references
References 54 publications
6
127
0
Order By: Relevance
“…Furthermore, as generalist foragers, bumble bees may avoid or dilute the negative effects of toxic phytochemicals by collecting pollen from multiple host-plant species (50,51). It is unclear, however, whether micronutrient variation in pollen or secondary plant metabolites can alter bee foraging for macronutrients or whether the concentrations of these compounds are somehow associated with the macronutrient levels we measured.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as generalist foragers, bumble bees may avoid or dilute the negative effects of toxic phytochemicals by collecting pollen from multiple host-plant species (50,51). It is unclear, however, whether micronutrient variation in pollen or secondary plant metabolites can alter bee foraging for macronutrients or whether the concentrations of these compounds are somehow associated with the macronutrient levels we measured.…”
Section: Discussionmentioning
confidence: 99%
“…Mixing pollen may dilute toxic compounds (Eckhardt et al 2014) or compose a diet closest to the bees' required optimum (which enables maximal possible individual or colony fitness), as the optimal ratio of nutrients (this is the stoichiometric relationship among all essential micro-and macronutrients that best supports an animal's metabolic functions and hence fitness) is hardly ever found in resources p r o v i d e d b y p l a n t s ( S i m p s o n a n d Raubenheimer 2012). If mixing was indeed used to balance the chemical composition of pollen loads, mixing at the individual forager level should be more pronounced in bee species which do not store pollen for longer periods but directly feed it to their young.…”
Section: Discussionmentioning
confidence: 99%
“…A multifloral pollen diet is generally considered better than a monofloral one. In the former the risk of a lack of essential amino acids is lower and the effects of eventual toxic or suboptimal pollens are balanced by the presence of favourable ones (Eckhardt et al, 2014). Moreover, Alaux et al (2010) found that a mixed pollen diet has a positive impact on the colony immunocompetence.…”
Section: Introductionmentioning
confidence: 99%